Pendidikan dan Pranata Sosial: Membentuk Masyarakat Masa Depan - Azfa Nabil Shafi; Hilalludin Hilalludin; Adi Haironi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Education is a crucial process in humanizing individuals, serving as a tool for individuals to interact effectively within their communities and society. Designed to develop self-improvement, enhance quality of life, and elevate individual dignity in pursuit of national goals, education plays a pivotal role. Social institutions, through their role in meeting societal needs, support the quality education process. This literature review highlights the importance of synergy between education and social institutions in shaping competent individuals who contribute positively to society. Utilizing a literature review method, data were gathered from various scholarly sources such as books, academic journals, and official documents. The findings underscore that education and social institutions are intertwined in developing character, knowledge, and skills among individuals. With support from families, communities, and the government, education can enlighten the nation and comprehensively develop the potential of learners. Innovative educational programs like e-books and e-learning, initiated by the government, signify positive steps in overcoming challenges and enhancing educational quality in Indonesia.